Geological conditions and reservoir characteristics of various shales in major shale-hosted regions of China - Shu-jing Bao; Tian-xu Guo; Jin-tao Yin; Wei-bin Liu; Sheng-jian Wang; Hao-han Li; Zhi Zhou; Shi-zhen Li; Xiang-lin Chen (China Geology)
China is home to shales of three facies: Marine shale, continental shale, and marine-continental transitional shale. Different types of shale gas are associated with significantly different formation conditions and major controlling factors. This study compared the geological characteristics of various shales and analyzed the influences of different parameters on the formation and accumulation of shale gas. In general, shales in China’s several regions exhibit high total organic carbon (TOC) contents, which lays a sound material basis for shale gas generation. Marine strata generally show high degrees of thermal evolution. In contrast, continental shales manifest low degrees of thermal evolution, necessitating focusing on areas with relatively high degrees of thermal evolution in the process of shale gas surveys for these shales. The shales of the Wufeng and Silurian formations constitute the most favorable shale gas reservoirs since they exhibit the highest porosity among the three types of shales. These shales are followed by those in the Niutitang and Longtan formations. In contrast, the shales of the Doushantuo, Yanchang, and Qingshankou formations manifest low porosities. Furthermore, the shales of the Wufeng and Longmaxi formations exhibit high brittle mineral contents. Despite a low siliceous mineral content, the shales of the Doushantuo Formation feature a high carbonate mineral content, which can increase the shales’ brittleness to some extent. For marine-continental transitional shales, where thin interbeds of tight sandstone with unequal thicknesses are generally found, it is recommended that fracturing combined with drainage of multiple sets of lithologic strata should be employed to enhance their shale gas production.©2024 China Geology Editorial Office.